The Effect of Benson Relaxation Technique on General Health of Patients with Multiple Sclerosis: A Randomized Controlled Trial - Saeed Mirhosseini; Mahboobeh Rezaei; Neda Mirbagher Ajorpaz (Golestan University of Medical Sciences, 2021)
Background: MS is a potentially disabling disease of the brain and spinal cord (central nervous system). Patients with MS have some problems in their general health. The purpose of this study was to determine the effects of Benson relaxation technique on general health in MS patients. Methods: This randomized controlled trial study was done on MS patients who registered in MS center in Kashan, Iran, from March 2017 to July 2018.  The first sixty eligible patients were recruited through convenient sampling method and then patients were randomly assigned to experimental and control groups. Patients in both groups were completed the Goldberg General Health Questionnaire (GHQ-28) before and after the intervention. Benson relaxation technique was performed by patients in the intervention group twice a day, 20 minutes per session, over a period of eight weeks. Data were analyzed using Chi-square, independent t-test, and paired t-test in the SPSS software (version 16). The level of signiﬁcance was set at 0.05. Results: There was signiﬁcant difference in the mean scores of general health before (44.22±12.4) and after (31.14±11.09) the intervention in the experimental group (P=0.002). After intervention, the difference between the mean difference scores of general health in the control (1.78±3.5) and experimental (13.08±2.88) groups was signiﬁcant (P=0.002). Conclusion: According to the ﬁndings, the Benson relaxation technique can be effective for improving MS patients' general health, physical and mental status, and social function. Due to the cost-effectiveness and safety of this technique, we propose the inclusion of the technique in the treatment protocol for MS patients.